An Emerging Molecular Understanding and Novel Targeted Treatment Approaches in Pediatric Kidney Diseases - Liebau, Max Christoph (Frontiers in Pediatrics, 2014)
The evaluation and treatment of the heterogeneous group of pediatric kidney diseases poses a challenging field in pediatrics. Many of the pediatric disorders resulting in severe renal affection are exceedingly rare and therapeutic approaches have remained symptomatic for most of these disease entities. The insights obtained from cellular and molecular studies of rare disorders by recent genetic studies have now substantially changed our mechanistic understanding of various important pediatric renal diseases and positive examples of targeted treatment approaches are emerging. Three fields of recent breathtaking developments in pediatric nephrology are the pathophysiology of nephrotic syndrome and proteinuria, the molecular mechanisms underlying atypical hemolytic uremic syndrome (aHUS), and the genetics and cellular biology of inherited cystic kidney diseases. In all three areas the combined power of molecular basic science together with deeply characterizing clinical approaches has led to the establishment of novel pathophysiological principles and to the first clinical trials of targeted treatment approaches.